Innovation on Laminated Bamboo Panel Flooring in Interior Design - Muhammad Zikrulyasin Norhazam,; Nuralya Azra Abdul Hafiz,; Nur Atasya Zakaria,; Salman Salim, (Multidisciplinary Applied Research and Innovation, 2022)
The usage of timber in construction has been increasing lately in the world, specifically in Malaysia. It will be lead to environmental destruction such as global warming.  People are not aware that there is another natural material which can replace wood and timber in construction that is bamboo. This study aims to evaluate usage of bamboo in building construction specifically, the technique installation of laminated bamboo panel flooring in the interior design field. The installation was made by gain more knowledge and information about the requirements of laminated bamboo panels. A design and pattern of the panels was made by using a software AutoCAD application. The new innovation was produced by the panel with allocation of the sizing, length and thickness. The floating technique was implemented for the installation of the panels rather than using of nail and glue. As a result, the new design and pattern innovation of laminated bamboo panels with the best and easy installation method has been introduced. These laminated bamboo panels can replace the timber or wood in the flooring design’s field because it has an aesthetic value and is eco-friendly too. It was recommended to the society to use the bamboo in construction all over the world rather than timber to reduce the greenhouse effect and simultaneously to save the earth. These laminated bamboo panels will be a high demand in the construction building in the future.